(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2006)
The applied problems of stability of soil constructions (hydrotechnical constructions) composed of swelling clays and those geotechnical peculiarities are discussed in the paper. The results of laboratory and field investigations have lead us to the following: the swelling properties of red-brown clays of Miocene, extended in Armenia, are result of those overconsolidation state and mineralogical composition (monthmorilonite clays); kaolinite clay soils at moistening get property of swelling at values W<WP, but bentonite clays - at values W >WP as well; the values obtained at laboratory investigations of swelling clays could not be applied in modeling of natural conditions. The swelling pressure and deformation in laboratory tests is greater than the same parameters in natural conditions (scale effect); the graph of relation between external pressure and swelling deformation has a form of curve line. The main part of swelling deformation (75-80%) in a body of dam can be compensated by external load that is less than the swelling pressure value; at headwaters the influence of swelling processes in a body of a dam is distributed up to depths 3,5-4 m from water surface.